Improvement and optimization of preparation process of seedling-growing bowl tray made of paddy straw - Lianhao, Li; Chun, Wang; Xinyue, Zhang; Guangyong, Li (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: A new type of rice seedling carrier named seedling-growing bowl tray made of paddy straw (SGBTMPS) was developed in China. Traditional preparation process for SGBTMPS is complex and difficult to operate. Hence, a new SGBTMPS preparation method has been developed by using straw powder as the main raw material. In this method, modified starch-based adhesive was replaced by the binder of thermosetting adhesive, and preparation constraints such as forming pressure, forming temperature, and dwell time were decreased. The effects of factors such as glue (modified starch-based adhesive), forming pressure, forming temperature and dwell time on SGBTMPS preparation were evaluated by single factor trial. Orthogonal trial and comprehensive weight analyses were adopted to optimize the parameters for SGBTMPS preparation. The results showed that optimal parameters were 125% glue and 1.2 kg mixed materials with the forming pressure, temperature, and dwell time of 30 MPa, 140℃ and 330 seconds, respectively. Compared with traditional preparation process, the proportioning link, preparation link, and preparation time in the new preparation process were reduced by 66.7%, 33.3%, and 17%, respectively; the pot-hole percentage and the expansion ratio were increased by 0.09% and 0.05%, respectively. This study indicated that the new preparation process for SGBTMPS was simpler and easier to operate and would provide a useful reference for further research and industrialization on SGBTMPS. Keywords: seedling-growing bowl tray, preparation process, paddy straw, rice production modified starch-based adhesive, straw powder DOI: 10.3965/j.ijabe.20140704.002 Citation: Li L H, Wan C, Zhang X Y, Li G Y. Improvement and optimization of preparation process of seedling-growing bowl tray made of paddy straw. Int J Agric & Biol Eng, 2014; 7(4): 13－22.